Reaction of squirrel monkeys to intratracheal inoculation with influenza/A/New Jersey/76 (swine) virus. - Berendt, R F (1977)
To determine whether a model could be established for laboratory investigations, nine squirrel monkeys were inoculated intratracheally with 10(7) median egg-infectious doses of influenza virus type A/New Jersey/8/76 (HSW1N1) (swine influenza virus). They responded with clinically detectable illness including fever, leukopenia, decreased food consumption, increased respiratory rate, occasional coughing, labored breathing, nasal discharge, and lethargy. Convalescence was well advanced by the day 10. All monkeys excreted virus for 7 to 8 days. A scoring procedure (illness score) has been developed for use in studies of vaccine and chemotherapeutic efficacy.